Training on the Implementation of EYD Rules Version V in Writing Scientific Papers for Teachers of Shohwatul Is'ad Islamic Boarding School Pangkep - Munira Hasjim; Lukman; Kaharuddin; Ita Suryaningsih; Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The training on the application of the latest version of the Indonesian Language Spelling Standard (EYD V) in writing scientific papers for teachers of Pondok Pesantren Shohwatul Is’ad Pangkep aims to improve their ability to write good and correct scientific papers in accordance with the latest version of EYD. The training was conducted through lectures, discussions, and writing exercises. The results of the training showed an improvement in understanding and application of the latest version of EYD in writing scientific papers. The teachers of Pondok Pesantren Shohwatul Is’ad Pangkep were able to write scientific papers better and correctly, and met the latest version of EYD. The conclusion of this training is the importance of applying the latest version of EYD in writing scientific papers for better understanding and universal recognition.